Clinical and radiological outcomes of acetabular revision with the Delta Revision TT cup. (November 2018) - Munegato, Daniele; Bigoni, Marco; Sotiri, Romeo; Bruschetta, Antongiulio; Omeljaniuk, Robert J; Turati, Marco; Andrea, Rossi; Zatti, Giovanni
Introduction: This study evaluates mid-term results of acetabular revision using a hemispherical acetabular cup in Trabecular Titanium with a cage construct. Methods: We reviewed 36 acetabular revisions performed with the Delta Revision TT cup in 34 patients (mean age = 75, range: 45–92 years). Acetabular defect types (Paprosky classification) included (1) 2B ( n = 5), (2) 2C ( n = 7), (3) 3A ( n = 15), and (4) 3B ( n = 9). Morcellised bone allografts were used in 24 cases, and synthetic bone used in 11. Outcomes were evaluated using the Harris Hip Score (HHS), and the Verbal Rating Scale (VRS) for pain measurement. X-ray visualisation of cup position was used to discern signs of mobilisation and bone graft incorporation. Survivorship at post-revision follow-up (mean = 39.8; range 12–91.5 months) was calculated. Results: HHS increased from 40.5 to 87 ( p < 0.01). 68% of cases were pain free; by comparison, 32% had an average VRS score of 1.9 (range 1–3). The average cup inclination angle was 40.8° (30–52°) postoperatively, compared with 41.2° (30–52°) at follow-up; there were no signs of loosening or mobilisation. Centre of rotation was fully restored in 21 (58.3%) hips. According to Gie classification; bone graft incorporation grades were (1) 3 ( n = 21), (2) 2 ( n = 12) and (3) 1 ( n = 2). The survival rate was 100% for aseptic loosening and 91.7% for any cause of revision. Conclusions: The Delta Revision TT cup promises good clinical and radiographic results at short- to mid-term follow-up, with high rates of survival rate and bone integration.